Multilingualism as racialization - Richardson, Jason; Stroud, Christopher (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
South African today remains a nation torn by violence and racial inequity. One of major challenges for its people is to create new futures across historically constituted racial divides, by finding ways to engage with each other across difference. In this regard, multilingualism holds out the promise of offering a way of bridging difference and opening spaces for engagement and empathy with Others. Today contemporary constructs of multilingualism, both in policy and everyday practice, continue to reinforce racialized divisions inherited from historical uses of language as a tool of colonialism, and a mechanism of governmentality in apartheid, the system of exploitation and state sanctioned institutional racism. In this paper we seek to demonstrate how multilingualism has always been, and remains today, an ‘epistemic’ site for managing constructed racialized diversity. In order to do so we trace periods of South Africa’s history. By way of conclusion, we suggest that alternative linguistic orders require a decolonial rethinking of the role of language(s) in epistemic, social and political life.